Petrology, geochemistry, and petrogenesis of two- pyroxene andesites in the northwest of Varzaghan (NW Iran): An evidence of calc- alkaline magmatism in a post- collisional setting - Morovvat Faridazad (پترولوژی, 2020)
The Ahar-Arasbaran Volcanic Belt (AAVB), in the Eastern Azerbaijan province, is located in the NW of Varzaghan. The area is a part of a large tectono-magmatic unit called Turkish-Iranian High Plateau (TIHP). The studied volcanic rocks composing of andesitic lavas and related pyroclastic deposits are the youngest volcanic rocks in the area. Mineralogically, these rocks are characterized by plagioclase, clinopyroxene and orthopyroxene as the main phenocrysts with dominant porphyritic texture. They have calc-alkaline to high-K calc-alkaline nature and on chondrite-normalized REE diagrams display less steep patterns (LaN/YbN=5.21-7.54) along with weak negative Eu anomaly (Eu/Eu*=0.82-0.89). The notable features of these rocks on MORB-normalized multi-element diagrams are LREEs and LILEs enrichment (i.e., Ba, Th, K, and Sr) relative to HREEs and HFSEs and TNT negative anomalies, which all are criteria of subduction-related magmas. The petrologic studies of above-mentioned rocks and their comparison with the comagmatic rocks from other places of TIHP (Ararat and Sahand) support this hypothesis that the parent magma of NW Varzaghan andesitic rocks was derived from partial melting of the subcontinental lithospheric mantle, which previously metasomatized by releasing fluids from subducting slab in a post-collisional setting and contaminated by upper continental crust during ascending to the surface.